PERSPEKTIF PEMBIAYAAN DALAM MENINGKATKAN KINERJA SEKOLAH (STUDI DESKRIPTIF KUALITATIF PADA SDN SINDANGSARI KECAMATAN PASEH KAB BANDUNG) - Dwi Yulia, Mira; Wasliman, Iim; Supyan Sauri, R. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is entitled “Financing Perspectives in improving School Performance (Qualitative Descriptive Study at SDN Sindangsari Kec Paseh Kab Bandung) Motivated by the existence of regulations on education, and finance, the results of the preliminary survey there are several problems faced in school financing, the purpose of this study is to find out the management process which includes strategy formulation, strategic planning, program preparation, perspective implementation, perspective monitoring related to financing. The method used is qualitative descriptive method, with interviews, observations and documentation studies as data collection techniques. Data Analysis Using Qualitative Descriptive Analysis Techniques with the use of predicates as well as data reduction, data presentation and conclusion drawing The results showed that overall the management process had been carried out by the school well, although there were several problems that arose including from human resources, bureaucracy, NGOs / journalists to the reporting process, For example, problems arose from differences in understanding between the Kabupaten BOS Management Team and the Inspectorate that resulted in misunderstandings, delays in disbursements, new applications that were not in accordance with the technical guidelines but had to be used, and one of the efforts to overcome these problems was Communication, Countermeasures, Coaching and Training, then a program related to improving the quality of teachers and managers of BOS funds was planned. Keywords: financing, school performance